Economic losses due to earthquake - induced structural damages in RC SMRF structures. Issue 1 (1st January 2017) - Rashid, Muhammad; Ahmad, Naveed
Abstract: This study presents the seismic performance assessment of reinforced concrete frame structures designed to modern buildings codes, for calculating the economic losses due to earthquake-induced structural damages. The structures investigated in the present research considered four (3, 5, 8, and 10 storeys) prototype special moment resisting frame (SMRF) structures designed to Uniform Building Code–97/Building Code of Pakistan. Quasi-static cyclic tests were carried out herein on special moment resisting beams in order to develop damage scale and beam reparability cost ratio. The considered structures were analyzed in a calibrated FE based software SeismoStruct using incremental dynamic analysis procedure employing a set of seven natural design spectrum compatible ground motion records. Damage to structural components was identified for each intensity level and integrated over the whole structure, with the required repair cost, to calculate the structure repair cost ratio (RCR). The structure RCR is correlated with the seismic intensity to develop seismic vulnerability curves, which can be used for the economic loss estimation (direct repairability cost) of SMRF structures given the seismic intensity.